Effect of rhynchophylline on contraction of rabbit aorta - Zhang Wei; Liu Guo-Xiong; Huang Xie-Nan (Acta Pharmacologica Sinica; Vol 8, No 5 (September 1987): Acta Pharmacologica Sinica, 2016)
The effects of rhynchophylline (Rhy) on the contraction induced by high K+, noradrenaline (NA) and Ca2+ were studied on the rabbit aortic strips, and the calcium antagonist verapamil (Ver) was used for comparison. Rhy and Ver inhibited both the contractions evoked by high K+ and NA； they shifted the concentration- response curves for KCl, NA and CaCl2 to the right, and depressed their maximal responses； the degree inhibited to high K+ was more potent than to NA. Rhy and Ver inhibited selectively potential-dependent Ca2+ channel (PDC). Both Rhy and Ver inhibited the fast contraction responses evoked by NA in Ca2+-free medium and did not cause any reduction of the slow sustained contraction response. This shows that both Rhy and Ver block the release of calcium from intracellular storage. These results suggest that Rhy, like Ver, may be a new calcium antagonist.